2017
DOI: 10.1186/s11671-016-1613-4
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport Properties of Polybenzimidazole and Poly(Phenylene Oxide) Mixed Matrix Membranes Incorporated with PDA-Functionalised Titanate Nanotubes

Abstract: Functionalised titanate nanotubes (TiNTs) were incorporated to poly(5,5-bisbenzimidazole-2,2-diyl-1,3-phenylene) (PBI) or poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) for improving the interfacial compatibility between the polymer matrix and inorganic material and for altering the gas separation performance of the neat polymer membranes. Functionalisation consisted in oxidative polymerisation of dopamine-hydrochloride on the surface of non-functionalised TiNTs. Transmission electron microscopy (TEM) confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…A comparison of the calculated diffusion coefficients, given in Table 6, with experimental data from Giel et al [10] and with molecular simulations performed by Fried et al [11] using the condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS) molecular mechanics force field is shown in Figure 11. Figure 11 proofs a proper prediction of diffusion coefficients of gas molecules in PPE using MD simulations.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A comparison of the calculated diffusion coefficients, given in Table 6, with experimental data from Giel et al [10] and with molecular simulations performed by Fried et al [11] using the condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS) molecular mechanics force field is shown in Figure 11. Figure 11 proofs a proper prediction of diffusion coefficients of gas molecules in PPE using MD simulations.…”
Section: Resultsmentioning
confidence: 98%
“…[3][4][5][6] In order to overcome the inherent limitations in its processability, [7] PPE is widely employed in the form of miscible or immiscible blends with a variety of other polymers. [7][8][9][10] When developing barrier or selective permeability solutions with PPE, it then becomes critical to screen the permeability properties of a multitude of formulations with PPE so as to balance permeability with processability. Computational chemistry can be leveraged very effectively in such scenarios to carry out an initial screening of the formulations before planning experimental formulation trials.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TiNTs compositions and structures may be practically unlimited and, by functionalization, their adhesion to polymer matrices can be improved. 38 A few studies have been performed for the use of TiNTs in reinforcement of polymer matrices. Reinforcement of a polymer composite film PEO/CS with 25 wt% content of TiNTs was found to be 2.6 times harder than the neat polymer blend and 3.4 times stiffer.…”
Section: Inorganic Nanotubesmentioning
confidence: 99%
“…functionalization with poly dopamine (PDA) improves the interfacial compatibility between the polymer matrix and inorganic material. 38 Silicon(Si) doped into the titanium dioxide nanotubes on Ti surface, using plasma immersion ion implantation, significantly enhanced the expression of genes related to osteogenic differentiation and improved bone-Ti integration. 78 Ion exchange of one-dimensional titanate nanotubes (TiONTs) can alter their biological activities.…”
mentioning
confidence: 99%